A splicing mutation in PHKG1 decreased its expression in skeletal muscle and caused PSE meat in Duroc × Luchuan crossbred pigs. (10th June 2019) - Liu, Y.; Liu, Y.; Ma, T.; Long, H.; Niu, L.; Zhang, X.; Lei, Y.; Wang, L.; Chen, Y.; Wang, Q.; Zheng, Z.; Xu, Xuewen
Summary: In recent years, Luchuan pigs in southern China have been used to produce high‐quality meat by crossbreeding them with Duroc boars; however, PSE (pale, soft and exudative) meat was frequently reported in the crossbred pigs, and the underlying reason remains unknown. We excluded the possibility of the well‐known causative mutations in RYR1 and PRKAG3 but identified the existence of an unfavorable allele of a splicing mutation (g.8283C>A) in PHKG1 in two Duroc boars and three Duroc × Luchuan crossbred pigs with PSE meat. An association analysis with 425 Duroc × Luchuan crossbred pigs revealed that the polymorphism of the splicing site of PHKG1 has significant association with the ultimate meat pH value ( P  =   0.035) and color score ( P  =   0.004). In addition, a strong cis‐eQTL (expression QTL) signal for the expression of PHKG1 was identified in 189 Duroc × Luchuan crossbred pigs, and the splicing mutation was proven to be significantly associated with the expression of PHKG1 ( P  =   4.01e‐11). Furthermore, RNA‐sequencing data analysis confirmed that 131 CC homozygotes had only one transcript (T1), with FPKM (fragments per kilobase of transcript per million) of 35.40 ± 7.28, and 58 CA heterozygotes had two types of transcripts (T1 and T2), with FPKM of 19.63 ± 5.11 and 9.20 ± 2.39 respectively. Based on the association and eQTL analysis results, we concluded that PSE meat in Duroc × Luchuan crossbred pigs is caused by the splicing mutation in PHKG1 . Our findings further support the effect of the causative mutation in PHKG1 on meat quality. The GEO accession number for the data is GSE124315.